Corrigendum to “Do cosmic-ray-driven electron-induced reactions impact stratospheric ozone depletion and global climate change?” [Atmos. Environ. 45 (2011), 3408–3514] - Grooß, Jens-Uwe; Müller, Rolf (Atmospheric Environment, 2013)
In the paper entitled “Do cosmic-ray-driven electron-induced reactions impact stratospheric ozone depletion and global climate change?” by Grooß and Müller (2011), the plot titles and the caption of Fig. 1 were not correct. The months for which the data were shown were not correctly indicated. The figure title included also the latitude range, within which the data were selected, while the data do not cover this complete latitude range especially they do not extend to the South Pole. The corrected figure titles show now the date and latitude range of the available data. Note also that the number of data points has increased slightly, due to additional ACE-FTS observations that have become available since the submission.